Cultures of Accountability in Indigenous Early Childhood Education in Mexico - Aldo Anzures Tapia (Universidade Federal do Rio Grande do Sul, 2020)
Accountability policies are meant to improve educational quality; yet, too often, they interfere with quality instruction, including bilingual instruction. Drawing on 18 months of ethnographic work in a multigrade Indigenous preschool in the Yucatan Peninsula in Mexico, I describe how Elisa, the teacher, principal and janitor, navigated demanding administrative tasks while implementing different governmental programs, placing on her a significant bureaucratic burden. Also, this led her to shift her attention from a culture of teaching-learning accountability to a culture of bureaucratic accountability. This study shows that early childhood education in Indigenous communities in Mexico depends on the astuteness and preparedness of frontline workers, such as teachers and school supervisors, as they keenly navigate the culture of bureaucratic accountability that governmental policies impose, while trying not to sacrifice an accountability to their own responsibility to the learners.